Efforts to Facilitate SDN Mekar Bakti Using the Fun Learning Method by KKN Students to Increase Student Learning Motivation - Muhammad Al Mighwar; Fitri Siti Nurazizah; Yosep Saepul Akbar; Rizky Rifaldy (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2025)
This journal is an actualization of the implementation of the national movement in educational, da'wah and psychological empowerment. This journal aims to adopt and apply the Fun Learning learning method in teaching in elementary schools. This journal also designs learning plans that integrate interesting and interactive elements to interact with students. Many strategies are used, such as educational games, interactive stories, and simple experiments. This strategy aims to create a pleasant learning experience. The method used in this paper is a qualitative approach with a case study design. The results of this study prove that there is a change in the effectiveness of students in learning using the fun learning method so the application of this method has an effect on increasing student motivation at SDN Mekarbakti.